TL - 18148 - Partial plantar fasciotomy for the treatment of plantar fibromatosis - Mansur, Nacime Salomão Barbachan; Azevedo, Rafael Mohriak de; Fonseca, Lucas Furtado; Silveira, Juliana Doering Xavier da; Raduan, Fernando Cepolina; Nery, Caio Augusto Souza (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Ledderhose’s disease (plantar fibromatosis) is an uncommon condition that usually affecting men older than 40 years of age and causes major discomfort and disability. The low response to conservative treatment and the progression of surgical techniques have motivated some professionals to resume considering surgical resolution for this disease. Our study describes the outcomes of a series of cases treated with resection of the affected band. Methods: This is a retrospective study with 14 patients (17 feet) diagnosed with plantar fibromatosis of the medial fascia that was refractory to conservative treatment and was treated surgically from December 2016 to November 2018. All patients were evaluated for improvement in symptoms, for major and minor complications and for relapse during the study period. Results: Our sample consisted of 9 men and 5 women with a mean age of 40.6 years (15-63 years). All patients showed medial fibromatosis and underwent subtotal fasciotomy of the medial fascial band with margins of at least 2 cm. Of the 17 feet, 5 showed relapse (29%) and only 2 required reintervention. Three patients (17%) developed surgical wound dehiscence, although all patients progressed to surgical wound closure with no need for surgical intervention. Two feet showed signs of medial plantar nerve injury, although the branch of the nerve was wrapped in fibromatosis and was also resected in those cases. Conclusion: Partial plantar fasciotomy is an alternative for the treatment of Ledderhose’s disease. Our series showed outcomes in line with those reported in the literature in terms of relapse and postoperative complications. The moderate relapse and reoperation rates should be considered when this procedure is indicated.